Pengaruh Arus Kas Bebas dan Profitabilitas terhadap Kebijakan Utang - Wati Aris Astuti; Nurlaelasari Nurlaelasari (Faculty of Economics and Business, University of Pasundan, 2013)
The decision to select the best source of funding for companies requiring careful analysis of company financial managers. Debt policyis one ofthe important funding decisions for companies that must always be considered so that the company’s financial statements to be optimal. Financial statements that will either enhance the reputation of the company that created the trust all stakeholders such as investors. Free cash flow and profitability is one of the ratios used to measure the financial performance of the company. On the basis of the phenomenon of the study aims to determine how much influence the free cash flow and profitability to debt policy on PT Intraco Penta Tbk (PT Inta).The method used in this research is descriptive and verification methods with quantitative approaches. The data used is the annual financial report of PT Inta for 7 years, from 2005 until 2011. The test statistic used is the calculation of Pearson correlation, multiple linear regression analysis with the classical assumptions. Results of analysis variables free cash flow and profitability have a significant effect and has a strong relationship with the positive direction of the debt policy on PT Intraco Penta Tbk.